Vietnam : Technical Assistance Report-Report on the National Accounts Mission. (IMF Staff Country Reports; Country Report ;, 2019)
This technical assistance report on Vietnam discusses evaluation of revised estimates of gross domestic product, to ensure that the compilation process is aligned with the System of National Accounts 2008 (2008 SNA) and that the methodology employed for estimation is consistent and coherent. This mission noted that the revisions follow recommendations of previous missions to implement the 2008 SNA to cover research and development and software will be treated as part of gross fixed capital formation. It is particularly important to conduct outreach to public and private data users to help them to understand the reasons for the revisions. Revisions to statistics are needed to consider changes in data sources and the economic structure. Revisions are a normal and expected part of national accounts compilation, reflecting additional information and new economic developments.